2009
DOI: 10.1371/journal.pone.0005947
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Angiogenic and Inflammatory Response in Glioblastoma by Hypoxia

Abstract: Glioblastoma are rapidly proliferating brain tumors in which hypoxia is readily recognizable, as indicated by focal or extensive necrosis and vascular proliferation, two independent diagnostic criteria for glioblastoma. Gene expression profiling of glioblastoma revealed a gene expression signature associated with hypoxia-regulated genes. The correlated gene set emerging from unsupervised analysis comprised known hypoxia-inducible genes involved in angiogenesis and inflammation such as VEGF and BIRC3, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 47 publications
4
84
0
Order By: Relevance
“…Based on a comprehensive analysis of PPN in human GBM and experimental models, it has been hypothesized that pseudopalisades comprise hypoxic tumor cells migrating away from dysfunctional vessels [2,28]. However, the presence of PPN does not directly correlate with hypoxia as suggested by gene expression profiles available for 50 patients of this cohort [21,22]. No correlation was observed with the previously identified hypoxia-induced gene expression signature, while the EGFR expression signature (G25) was significantly associated with the presence of PPN (p = 0.02).…”
Section: Discussionmentioning
confidence: 95%
“…Based on a comprehensive analysis of PPN in human GBM and experimental models, it has been hypothesized that pseudopalisades comprise hypoxic tumor cells migrating away from dysfunctional vessels [2,28]. However, the presence of PPN does not directly correlate with hypoxia as suggested by gene expression profiles available for 50 patients of this cohort [21,22]. No correlation was observed with the previously identified hypoxia-induced gene expression signature, while the EGFR expression signature (G25) was significantly associated with the presence of PPN (p = 0.02).…”
Section: Discussionmentioning
confidence: 95%
“…Inflammation has been shown to be critical for promoting apoptosis resistance, proliferation, invasion, metastasis and secretion of proangiogenic and immunosuppressive factors in tumors of different origins, including lung (Peebles et al, 2007), prostate (Stock et al, 2008), breast (Hu and Polyak, 2008), stomach (Correa and Houghton, 2007), pancreas (Chu et al, 2007), gut (Quante and Wang, 2008) and, of course, the brain (Murat et al, 2009;Paugh et al, 2009). Thus, it is easy to imagine how the brain parenchyma of an AD patient, which is rich in proinflammatory mediators, would be a good environment for the development and progression of brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed distinct phenotypic states or subtypes that stratify gliomas and resemble different glial lineages (1)(2)(3). Although immunological gene expression classifications have been associated with clinical outcomes and prognosis (4,5), precision immunotherapy will ultimately rely on manipulation of the T-cell population that infiltrates gliomas and its underlying repertoire of T-cell receptors (TCRs). However, the structure and intertumoral heterogeneity of the TIL population in gliomas has not been described.…”
mentioning
confidence: 99%